VACUUM HEAT TREATMENT OF ENGINEERING MATERIALS; THE TECHNICAL ASPECT - Khan, S; Khan, M A; Haq, A ul- (Biological Sciences - PJSIR, 2001)
In view of the rapid technological development taking place around the globe, advanced materials processing comes into sharp focus. Heat treatment in vaccum offers a plausible alternative over conventional heat treatment process as the former allows to heat treat finished parts and components with minimum surface degradation. The paper reviews various vacuum heat treating processes and their advantages over the conventional processes with specific reference to nuclear, missile and aerospace materials.